The role of religious belief in the military - Saadoun Koh, Najat; Aboud Sammar, Saad (Journal of College of Education, 2022)
Summary: This study sheds light on the most important doctrinal matters and their role on the Hittite military institution and their importance in terms of their impact on the wars that the Hittite kings were waging in motivating those forces, the support of the gods and their support for the king and the war he will wage, and the effect of sanctity in wars